Biowaste‐Derived, Self‐Organized Arrays of High‐Performance 2D Carbon Emitters for Organic Light‐Emitting Diodes. Issue 10 (27th January 2020) - Singh, Amandeep; Wolff, Annalena; Yambem, Soniya D.; Esmaeili, Mostafa; Riches, James D.; Shahbazi, Mahboobeh; Feron, Krishna; Eftekhari, Ehsan; Ostrikov, Kostya (Ken); Li, Qin; Sonar, Prashant
Abstract: Low‐cost flexible organic light‐emitting diodes (OLEDs) with nanoemitter material from waste open up new opportunities for sustainable technology. The common emitter materials generated from waste are carbon dots (CDs). However, these have poor luminescent properties. Further solid‐state emission quenching makes application in display devices challenging. Here, flexible and rigid OLED devices are demonstrated using self‐assembled 2D arrays of CDs derived from waste material, viz., human hair. High‐performance CDs with a quantum yield (QY) of 87%, self‐assembled into 2D arrays, are achieved by improving the crystallinity and decreasing the CDs' size distribution. The CD island array exhibits ultrahigh hole mobility (≈10 −1 cm 2 V −1 s −1 ) and significant reduction in solid‐state emission quenching compared to pristine CDs; hence, it is used here as an emitting layer in both indium tin oxide (ITO)‐coated glass and ITO‐coated flexible poly(ethylene terephthalate) (PET) substrate OLED devices, without any hole‐injection layer. The flexible OLED device exhibits a stable, voltage‐independent blue/cyan emission with a record maximum luminescence of 350 cd m −2, whereas the OLED device based on the rigid glass substrate shows a maximum luminescence of 700 cd m −2 . This work sets up a platform to develop next‐generation OLED displays using CD emitters derived from the biowaste material. Abstract : Carbon‐based nanomaterial derived from human‐hair biowaste is used as an emitter for organic light‐emitting diodes (OLEDs) and sets up a new platform for display industries seeking sustainable technology. These flexible and rigid substrate OLEDs demonstrate ways to accomplish low‐cost, stable and voltage‐independent emission and high luminescence, powered by a greater quantum yield (QY) in the solid state, resulting from controlled nanoparticle self‐assembly.